A new pathway to displacement? The implications of less-than-unanimous strata renewal laws for vulnerable residents. Issue 4 (2nd October 2020) - Crommelin, Laura; Easthope, Hazel; Troy, Laurence; Randolph, Bill
ABSTRACT: Multi-unit developments have been a feature of Australian cities for decades, particularly Sydney. As these buildings age, commercial and planning drivers promote redevelopment, but renewing private multi-unit housing poses significant and unique problems, as this housing is typically under multiple ownership (e.g., strata title). Jurisdictions worldwide have responded by changing laws to allow redevelopment with less-than-unanimous consent of all unit owners, meaning a majority of owners can vote their neighbours out of their homes against their will. In New South Wales, legislation introduced in 2015 enabled the redevelopment of strata titled property with the consent of 75% of owners. Research conducted at the time highlighted a range of risks, especially for vulnerable groups like lower-income and elderly residents. With the legislation now due for a statutory 5-year review, it is timely to revisit the research findings and examine subsequent developments, to identify key issues for policymakers when assessing the impact of the law's first five years. These issues should be of interest not only in NSW, but in all three Australian jurisdictions with less-than-unanimous renewal laws, as well as many international cities.